2015
DOI: 10.4236/gep.2015.34002
|View full text |Cite
|
Sign up to set email alerts
|

Resource Potentials of Composting the Organic Wastes Stream from Municipal Solid Wastes Compositions Arising in Nigerian Cities

Abstract: The paper presented an assessment of the resource potentials of composting organic waste materials arising from the municipal solid waste stream from cities in Nigeria. Through a review of quantitative data, the composition of municipal solid waste arising within cities in Nigeria was examined in order to identify the potentials for composting organic materials from the waste stream composition. The data showed that the average majority of the waste stream was organic materials which implied high potentials fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
(32 reference statements)
1
6
0
2
Order By: Relevance
“…Lenox et al [ 24 ] reported a cellulose concentration of 53 % and suggested that high resistant to biodegradation by sawdust was due to its high cellulose and lignin content. The initial contents of nitrogen in the sewage sludge (5.16 %), Chicken litter (4.96 %) and vegetable waste (5.9 %) were in conformity with what was presented by Harir et al [ 25 ] and Asadu et al [ 26 ] with the same organic wastes and suggested that the percentages were sufficiently high to maintain the microbial growth for biodegradation during composting. High concentration of organic matter in all the wastes sludge confirms that they are biodegradable and good substrates for production of biofertilizer.…”
Section: Resultssupporting
confidence: 88%
“…Lenox et al [ 24 ] reported a cellulose concentration of 53 % and suggested that high resistant to biodegradation by sawdust was due to its high cellulose and lignin content. The initial contents of nitrogen in the sewage sludge (5.16 %), Chicken litter (4.96 %) and vegetable waste (5.9 %) were in conformity with what was presented by Harir et al [ 25 ] and Asadu et al [ 26 ] with the same organic wastes and suggested that the percentages were sufficiently high to maintain the microbial growth for biodegradation during composting. High concentration of organic matter in all the wastes sludge confirms that they are biodegradable and good substrates for production of biofertilizer.…”
Section: Resultssupporting
confidence: 88%
“…NCC has unlimited illegible dumpsites, evident in the case of Ngomongo [26][27][28]. Importantly, waste recycled to reduce the pollution on the environment, provide job opportunities, as evident in developed countries, to address the challenges of SWM [16,29]. There is an institutional framework lapse in the recycling of waste, no mechanism for separating waste, no capacity at source, and the household level, no waste separation.…”
Section: Discussionmentioning
confidence: 99%
“…The actors, the public, civil society, NCC, NEMA, and ministries of environment and Natural resources and Water Resource Authority [30,31]. Indiscriminate disposal by the public shows the absence of public education on SWM focusing on critical areas, for instance, proper waste disposal, waste reduction, and environmental stewardship [29,32]. Also, insu cient institutional, nancial capacities, and management systems affect performance, restraining the interpretation of policy and legislation on SWM in practice [24,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatif, TKKS dapat dijadikan bahan baku dalam proses pengomposan [5]. Pengomposan adalah proses penguraian limbah organik secara biologis dengan bantuan mikroorganisme secara aerobik menjadi zat humus [6]. Proses pengomposan dapat dipengaruhi oleh beberapa parameter seperti nutrisi, rasio C/N, ukuran bahan kompos, suhu, pH, kadar air, dan frekuensi pembalikan [7].…”
Section: Pendahuluanunclassified